2019
DOI: 10.1186/s13007-019-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling maize above-ground biomass based on machine learning approaches using UAV remote-sensing data

Abstract: BackgroundAbove-ground biomass (AGB) is a basic agronomic parameter for field investigation and is frequently used to indicate crop growth status, the effects of agricultural management practices, and the ability to sequester carbon above and below ground. The conventional way to obtain AGB is to use destructive sampling methods that require manual harvesting of crops, weighing, and recording, which makes large-area, long-term measurements challenging and time consuming. However, with the diversity of platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
239
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(245 citation statements)
references
References 67 publications
(64 reference statements)
5
239
0
1
Order By: Relevance
“…This research furthermore showed that there are limitations to the biomass estimation for certain crops and that models developed for a specific crop cannot directly be used for other crops, and generic models should be used with care. For a fully operational approach, an effort should be made towards combining LiDAR with hyperspectral data, as mentioned by [22,23,26], so models can be trained for a range of crops. This will increase both the accuracy and general applicability of high-throughput biomass estimation models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research furthermore showed that there are limitations to the biomass estimation for certain crops and that models developed for a specific crop cannot directly be used for other crops, and generic models should be used with care. For a fully operational approach, an effort should be made towards combining LiDAR with hyperspectral data, as mentioned by [22,23,26], so models can be trained for a range of crops. This will increase both the accuracy and general applicability of high-throughput biomass estimation models.…”
Section: Discussionmentioning
confidence: 99%
“…Using, for example, a PLS regression as mentioned in [21], or using machine learning approaches like [22], where a deep convolutional network was used to predict biomass using RGB imagery. Or the machine learning approach of [23], where they used a range of spectral indices as predictors to estimate above ground biomass with an NRMSE of 24.95%. Combining these different methodologies with a predictor such as the 3DPI indicator could result in a better prediction of biomass.…”
Section: Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Small, low-cost unmanned aerial systems (UAS) and satellite technologies (mainly equipped with multispectral sensors) are mainly deployed to execute the phenotyping task. The UAS system allows proximal sensing of plant phenotypes at a small experimental unit level with high spatial and spectral resolution [20][21][22].Another alternative extensively used to estimate herbage yield is plant height [23][24][25]. Plant structural information metrics may be accessed from terrestrial and aerial sensors.…”
mentioning
confidence: 99%
“…UAS height estimates of maize have previously been validated using correlations to traditional manual measurements and evidence of equivalent or greater phenotypic variation partitioned to genetic factors [7, 9, 15, 16]. To our knowledge the majority of reported field based phenotyping of maize with HTP platforms has focused on hybrid trials [6-9, 15, 17-19] but, limited reports have been published on the evaluation of inbred trials [2022], specifically genetic mapping populations. Inbred lines in maize are substantially shorter and have less biomass than hybrids, lacking heterosis.…”
Section: Introductionmentioning
confidence: 99%